Los procesos administrativos financieros y su incidencia en el gasto público en la Universidad Técnica de Babahoyo, 2021 - Barros Vera, Jennifer Mariel (2023)
The financial administrative processes that are implemented are crucial in any institution and even more of a public nature, which leads to permanent optimization, because their progress depends on it. This investigation is based on being able to identify if the financial administrative processes affect public spending through the different functions that are fulfilled in the departments involved. The general objective of the study is based on determining the way in which financial administrative processes affect public spending at the Technical University of Babahoyo, 2021, the research method is of the applied type because they can contribute new events, with a mixed approach for the complexity that it represents, with a descriptive, causal explanatory scope and with a non-experimental design of cross-sectional cost. As the main instrument of data collection in the present investigation we have the survey that will allow us to know the different opinions of the respondents. Additionally, it is mentioned that for the data processing the statistical tool IBM SPSS and Excel were used, showing the different opinions of the 77 respondents.